2002
DOI: 10.2337/diabetes.51.12.3353
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Childhood Type 1 Diabetes in the 20th Century

Abstract: The incidence of childhood type 1 diabetes increased worldwide in the closing decades of the 20th century, but the origins of this increase are poorly documented. A search through the early literature revealed a number of useful but neglected sources, particularly in Scandinavia. While these do not meet the exacting standards of more recent surveys, tentative conclusions can be drawn concerning long-term changes in the demography of the disease. Childhood type 1 diabetes was rare but well recognized before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
361
1
12

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(379 citation statements)
references
References 65 publications
5
361
1
12
Order By: Relevance
“…Although vitamin D supplements are advised in many countries, the application is far from strictly controlled and many times, these supplements are omitted or administered irregularly. Nutritional rickets that has never been completely eradicated in some countries and may be reappearing in industrialised countries [23] could be one of the factors contributing to the higher incidence of Type 1 diabetes in the past two decades [24]. A recent Finnish epidemiological study [17] has shown a clear association between overt rickets in the first year of life in this genetically high-risk population and the development of diabetes in later life.…”
Section: Discussionmentioning
confidence: 99%
“…Although vitamin D supplements are advised in many countries, the application is far from strictly controlled and many times, these supplements are omitted or administered irregularly. Nutritional rickets that has never been completely eradicated in some countries and may be reappearing in industrialised countries [23] could be one of the factors contributing to the higher incidence of Type 1 diabetes in the past two decades [24]. A recent Finnish epidemiological study [17] has shown a clear association between overt rickets in the first year of life in this genetically high-risk population and the development of diabetes in later life.…”
Section: Discussionmentioning
confidence: 99%
“…6 Experimentally, a number of helminth parasites, including the trematode Schistosoma mansoni and the nematodes Heligmosomoides polygyrus and Trichinella spiralis, prevent the onset or suppress the severity of type 1 diabetes in non-obese diabetic (NOD) mice, [12][13][14] experimental autoimmune encephalitis 15 and experimental colitis. [16][17][18] A clinical trial demonstrated that oral administration of porcine whipworm eggs improves symptoms in patients with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The prevalence of type 1 diabetes and other autoimmune diseases has increased dramatically over the past few decades. [4][5][6] An analysis of 37 epidemiological studies conducted from 1960 to 1996 reports that there has been an increase in the incidence of type 1 diabetes worldwide of 3% per year over that time period, and that by the year 2010 the incidence of type 1 diabetes may be as high as 50/100 000 persons in some developed countries. 7 While genetic factors may play a role in susceptibility to type 1 diabetes, it is probable that the dramatic worldwide increase in type 1 diabetes prevalence is the result of environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the incidence of Type 1 diabetes over the past few decades has been reported worldwide [1,2,3,4]. estimated population of 1.9 million.…”
Section: Introductionmentioning
confidence: 99%